Clinical response with antibiotics of 37 cases of acute pyogenic meningitis in Pediatrics (from 3- 12 years) - Kakar, Behram; Kakar, Bashir Ahmed; Durrani, Asmat (Annals of King Edward Medical University, 2016)
Over a period of one year 37 confirmed cases of acute pyogenic meningitis by latex agglutination method were admitted in department of paediatrics, Liaquat Medical College Hospitals (LMCH) Jamshoro Hyadrabad, Sindh. These patients were treated with various antibiotics with the result that ampicillin plus chloromycetin is in combination as is effective as cephalosporin up to the age of 4 years and up to 12 years ampicillin as ampicillin plus chloromycetin which is standard treatment.